2003
DOI: 10.1002/pola.10634
|View full text |Cite
|
Sign up to set email alerts
|

Helicity induction on a poly(phenylacetylene) derivative bearing aza‐18‐crown‐6 ether pendants in water

Abstract: A stereoregular poly(phenylacetylene) bearing the bulky aza-18-crown-6 ether as the pendant (poly-1) formed a predominantly one-handed helical conformation upon complexation with various chiral compounds, such as amino acids, peptides, aminosugars, amines, and amino alcohols in water. The complexes exhibited an induced circular dichroism (ICD) in the UV-visible region of the polymer main chain. Therefore, poly-1 can be used as a novel probe for determining the chirality of chiral compounds in water. The assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…The first example was reported for poly(phenylacetylene) with aza-18-crown-6 (2), in which a macromolecular helicity was induced on the main chain through the host-guest complexation with the perchlorate salts of amino acids [27,28]. For this helicity induction system, an unprecedented sensitivity was observed, that is, the polymer could respond to an extremely small amount of chiral information.…”
Section: Helicity Inductionmentioning
confidence: 99%
“…The first example was reported for poly(phenylacetylene) with aza-18-crown-6 (2), in which a macromolecular helicity was induced on the main chain through the host-guest complexation with the perchlorate salts of amino acids [27,28]. For this helicity induction system, an unprecedented sensitivity was observed, that is, the polymer could respond to an extremely small amount of chiral information.…”
Section: Helicity Inductionmentioning
confidence: 99%
“…In addition, Takeishi et al25 reported that for a helical polyamide consisting of atropisomeric binaphthyl units and crown ether rings, the complex formation of crown ether with metal cation caused a conformational change. Recently, Yashima and coworkers27–29 and we30, 31 accomplished the macromolecular helicity induction of poly(phenylacetylene)s and poly(phenyl isocyanate)s bearing crown ether, respectively. These polymers formed the one‐handed helical structure in the main chain through the host–guest complexation with optically active guests, in which crown ether oriented in the helical array based on the polymer helix axis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research indicates that chiral ammonium salts have an effect on polymers with flexible main chain structures, such as poly(phenylacetylene) and poly(isocyanate). [17][18][19][20][21][22][23][24][25] In this study, we investigated the effect of adding a chiral ammonium salt to the maleimide polymer with a rigid main chain structure. Because the main chain structure is rigid, there is no space between the bulky N-substituents, including a crown ether unit.…”
Section: Optical Properties Of Polymersmentioning
confidence: 99%
“…Recently, polymers bearing various crown ethers have been investigated. For example, Yashima and co-workers [18][19][20][21][22] and Kakuchi and co-workers [23][24][25][26] reported that poly(phenylacetylene) and poly(isocyanate) bearing an aza crown ether or a benzo crown ether induced a one-handed helical structure upon the addition of chiral alkyl ammonium salts, chiral amino alcohols and chiral amino acids.…”
Section: Introductionmentioning
confidence: 99%